The Making Organic Fertilizer from Cow Manure Using the Composting Method - Suwarsito Suwarsito; Aman Suyadi; Hindayati Mustafidah (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Most of the agricultural cultivation activities of the Sambirata Village community still use inorganic fertilizers. Continuous inorganic fertilizers can cause physical, chemical, and biological damage to the soil and reduce land productivity. The purpose of this community service activity is to increase the knowledge and skills of the Sambirata Village farmer group in making organic fertilizer using the composting method with coactivators. Partners of community service activities are Kridoyuwono farmer groups in Sambirata Village, Cilongok District, Banyumas Regency. The implementation of community service activities uses an active participation approach. Partners of community service activities are expected to actively participate in all series of activities, starting from preparation, implementation of training, and hands-on practice. At the end of the activity, an evaluation was carried out to determine the level of understanding of the training material using pretest and posttest instruments. The results of community service activities can increase the knowledge and skills of farmer groups in Sambirata Village for making organic fertilizers using the composting method with bioactivators. The members of the farmer group have been able to practice making organic fertilizer from cow dung using the composting method properly and correctly.